Comparison of the Effect of Intra-Articular Injection of Autologous (Orthokine) Interleukin-1 Receptor Antagonist (IL-1Ra) and Hyaluronic Acid in Pain Control of Knee Osteoarthritis - Hashemi, Masoud; Taheri, Mehrdad; Adlkhoo, Hossein; Dadkhah, Payman; Abbasian, Mohammad Reza (Novelty in Biomedicine, 2019)
Background: Due to the limitations of more common treatments of osteoarthritis, pharmaceutical research has been increasingly conducted during the past two decades with the aim of determining the rate of recovery of the disease’ symptoms and making the process of disease progression slow. The purpose of this study was to compare the effect of intra-articular injection of autologous interleukin-1 Receptor Antagonist and hyaluronic acid in pain control of knee osteoarthritis. Materials and Methods: A total of 60 patients with knee osteoarthritis were allocated to two groups of 30 in this randomized double-blind clinical trial. In the intervention group, injection of 2 milliliter of interleukin-1 receptor antagonist (Orthokine) into the knee joint was performed three times at intervals of one week (base time, seventh day and fourteenth day). In the control group, three injections of two milliliters of hyaluronic acid solution into the knee joint were performed at intervals of one week. Pain, symptoms, daily activities, sport-recreational performance, and knee-related quality of life were five outcomes investigated by completing two questionnaires, the knee injury and osteoarthritis outcome score (KOOS), Western Ontario, and McMaster Universities Arthritis Index (WOMAC) by the patients on two occasions before the start of treatment and six months after the last injection. Repeated measure and t-test were statistical tests used in this study. Results: The mean score of pain in the first month (p=0.005) and the sixth (p=0.049) in the intervention group was less than the control group. Based on the scores of the KOOS questionnaire, the mean score of symptoms (p=0.006), daily activities (p=0.001) and sport-recreational performance (p=0.037) in the Orthokine group were higher than the hyaluronic acid group after six months. Also, the results of the questionnaire WOMAC show that while before the start of treatment, the mean of physical performance in the Orthokine group is greater than the control group, there is no difference in any of the indicators of pain, dryness of the joint, physical performance, and total score (p=0.319) in the sixth month. Conclusion: According to the findings of this study, it seems that Orthokine has beneficial biological effects in patients with knee osteoarthritis. Intra-articular injection of Orthokine is a low invasive, safe and effective method, which can be considered as an appropriate choice in patients with chronic knee pain.